Anglo-American Diplomacy to Prevent Franco’s Spain from entering the War on the Axis Powers side and to neutralize its Colonial Ambition in North Africa: 1940-1942 - Brahim HAROUNI (Revue des Sciences Humaines)
The Anglo-American apprehension about the Spanish attitude, with respect to the landing in North Africa in 1942, was amply justified. Indeed, the strategic and commending position of Spain over the Straits of Gibraltar made an attack by Franco against the Straits, with German assistance, feasible and likely. If such a move were to take place during the landing operations in Morocco and Algeria, the situation for the expeditionary forces would be disastrous with far reaching consequences. With the likelihood of such prospects, it became necessary to neutralize Spain. The neutralization of Spain was left to the British who had better relations with Spain than the United States. The present article attempts to shed light on the way the British conducted this mild approach in the midst of a totally torn Europe.